A Study on Centrobolus titanophilus Size Dimorphism Shows Width-Based Variability - Cooper, Mark (New Visions in Biological Science Vol. 8, 2022)
The present research aimed to study the sexual size dimorphism of Centrobolus titanophilus. Diplopoda illustrated reversed sexual size dimorphism (SSD) where one sex was larger than another. The SSD of C. titanophilus was shown from data taken in the Cape Province, South Africa. The average size of C. titanophilus was 285 41.875 mm (n=8); the smaller sex was 276.6667 40.6667 mm (n = 5) and the larger sex was 290 42.6 mm (n = 3). The absolute size was estimated (x=418.3596 mm3; y=359.3327 mm3) and used to calculate the difference between the sexes based on differences in tergite width (t=1.85901, p=0.084172, n=8). The SSD ratio for C. titanophilus was 1.164268 which differed from 1 (t=2.70801, p=0.012845, n=8).